2015
DOI: 10.3855/jidc.5507
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Leptospira interrogans serovar Pomona isolated from swine in Brazil

Abstract: Introduction: Leptospira interrogans swine infection is a cause of serious economic loss and a potential human health hazard. In Brazil, the most common serovars associated with swine infections are Pomona, Icterohaemorrhagie and Tarassovi. Cross-reactions among serovars and the failure of infected animals to seroconvert may complicate the interpretation of serological tests. Molecular methods with better discriminatory powers are useful tools for swine leptospirosis characterization and diagnosis. Methodology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 27 publications
0
13
0
1
Order By: Relevance
“…The incidence of human leptospirosis has increased from 0.2 cases /100 000 people in 2005 to 1.0 cases /100 000 in 2015. It is a disease caused by Leptospira, a Gram-negative aerobic bacterium belonging to the Spirochaetaceae family [1,2,4,7,[29][30][31]. Seroepidemiological surveys carried out by the Institute of Public Health (IPH) in the period 1980-1990 in Albania have demonstrated a predominant circulation of species, Leptospira Pomona and Leptospira ichterohaemorrhagica [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of human leptospirosis has increased from 0.2 cases /100 000 people in 2005 to 1.0 cases /100 000 in 2015. It is a disease caused by Leptospira, a Gram-negative aerobic bacterium belonging to the Spirochaetaceae family [1,2,4,7,[29][30][31]. Seroepidemiological surveys carried out by the Institute of Public Health (IPH) in the period 1980-1990 in Albania have demonstrated a predominant circulation of species, Leptospira Pomona and Leptospira ichterohaemorrhagica [11].…”
Section: Discussionmentioning
confidence: 99%
“…Leptospirosis is a re-emerging disease with worldwide distribution, with higher incidence in the developing world [1][2][3][4]. The disease is encountered in both urban and rural settings in countries with tropical, subtropical, or mild climate.…”
Section: Introductionmentioning
confidence: 99%
“…The finding of identical VNTR patterns circulating between animals and humans is not unexpected and has been described for serovar Pomona genotype A obtained from pigs in Brazil (Miraglia et al . ). It is expected that the extensive usage of VNTR and the description of new patterns will probably lead to more matches between strains of different hosts, allowing a clearer scenario of the circulation of leptospiral strains.…”
Section: Resultsmentioning
confidence: 97%
“…is long and complex, that the period of leptospiruria varies and is not constant during the day, and because animals can be in the acute phase of the disease and have not started to eliminate the microorganism [19], and although serological tests are the most used, it is necessary the combination with direct detection tests like the isolation through culture or molecular techniques to provide a definitive and individual diagnosis and understand the distribution of the microorganism in the population [40]. Culture-positive results but negative to MAT, 7.5% (3/40) obtained in this study, can be explained because when the infection is endemic in farms can be found sows with titers <100; also, should be aware that the MAT test has limitations and there is not always correlation between the found serogroups and the results in the isolation and subsequent identification [16,27,49].…”
Section: Discussionmentioning
confidence: 97%
“…Globally, Leptospira isolation from pig urine has only been performed in countries like Brazil [19,27], Tanzania [24] and Thailand [25]. The main objective of this study was to relate the behavior of the reproductive indicators with the presence of Leptospira spp.…”
Section: Introductionmentioning
confidence: 99%